ANALISIS FAKTOR-FAKTOR MOTIVASI YANG BERPENGARUH TERHADAP PRESTASI KERJA (STUDI KASUS RSUP DR. SOERADJI TIRTONEGORO KLATEN) - , Sukma Prima Yudha., S.Farm ([Yogyakarta] : Universitas Gadjah Mada, 2013)
in Motivation an organization or company aims to encourage morale to want to work hard to provide all of the capabilities and skills for the creation of an organization. Leaders who lead through motivation will create conditions that employees are inspired to work hard. Employees who have high motivation is essential if the results of performance to be achieved consistently. leadership Leaders will take a that reflects an awareness that employee productivity through the main part and can not be substituted to achieve organizational goals. Motivation of workers will differ according to the level of education and economic conditions. People who are more educated and more economically independent, the source of motivation will be different, no longer solely determined by means of motivation but also influenced by the need. Motivate subordinates by giving responsibility and broad opportunities for employees to take decisions in completing the work. Motivation is very important for the motivation of each employee is expected to work hard and enthusiastically to achieve high labor productivity (Hasibuan, 2001). Motivation will provide inspiration, encouragement, morale for employees thus established a good working relationship between employees and management so that organizational goals can be achieved to the fullest. research The was conducted by giving questionnaires to as many as 194 research subjects who are permanent employees and have worked at least 2 years in the department of Dr. Soeradji Tirtonegoro Klaten. Kuisiner the questionnaire used consists of motivational factors and job performance. Questionnaires were then tested the validity and reliability of the 30 respondent who proceed to regression analysis to see how the motivational factors that influence job performance using SPSS 15 for windows. afiliasi The results showed that the coefficient of determination (R square) = 0.249 or 24.9% at 24.9% means that work performance is affected by several variables, achievement motivation, motivation , competence and motivation motivational power, sedangkan76, 1% other affected by other factors outside the study variables with the regression equation Y = 0.766 +0.139 (X1) + 0.210 (X2) + 0.244 (X3) +0.300 (X4).